INTELLIGENZ STRUKTUR TEST DAN STANDARD PROGRESSIVE MATRICES: (DARI KONSEP INTELIGENSI YANG BERBEDA MENGHASILKAN TINGKAT INTELIGENSI YANG SAMA) - Retno Kumolohadi; Miftahun Ni’mah Suseno (UII, 2012)
This study aimed to correlate between output test from Intelligenz Struktur Test (IST) and Standard Progressive Matrices (SPM). These tests measure intellectual capacity. SPM is intelligence test that has been formed set of pictures A, B,C,D. Subject must continue and complete that picture so that reflected his/her abstract reasoning. SPM is a general test, however IST is a special test but the two test produce IQ score. IST has been formed nine aspect: SE (complete sentences), WA (complete word), AN (similarity of words), GE (the same things that belongs to), RA (numerical reasoning), ZR (line of numeric), MA (choice of shape), WU (design of beam), ME (read of symbol). Subject of this research was university student of department of Psychology Islamic University of Indonesia. They did classical test of two measured test. Coefficient correlation between two test is 0.336; p – 0.000 (p